Principles for designing activity-based personalized eLearning - BRADY, AOIFE; CONLAN, OWEN; O'KEEFFE, IAN BRIAN; WADE, VINCENT PATRICK (IEEE Computer Society, 2007)
Activity-based Personalized eLearning involves delivering to a learner a learning experience that is tailored to their individual needs. Traditionally, these needs have been met through the personalized selection of content that fits the learner?s preferences. However, by coupling this approach with the possibilities of interactive services a more engaging form of personalized education may be realized. This paper describes the design principles for producing activity-based personalized distance learning offerings.
PUBLISHED
Keywords: computer aided instruction; distance learning